MESSAGE FRAMING AND SOURCE CREDIBILITY IN FUNCTIONAL FOOD ADVERTISEMENTS (Proceeding Fakultas Ekonomi, 2012)
This study sought to investigate the influence of message framing and source credibility on consumer risk perception on functional food products. See the inconsistencies in previous studies, the problems in this study were a) Which is more effective positive or negative message framing in a functional food product advertising; b) Which is more effective high or low source credibility in the functional food product advertising? The general objective of this study was to analyze the use of message framing and source credibility of the right to use in functional food product advertising. Research strategy used by researchers is the experimental method. In this study selected participants were adults. Participants were chosen voluntary. In the selection of group experiments was with randomized assignment. Testing hypotheses 1 and 2 with one way ANOVA, while the third hypothesis testing with two ways ANOVA. So the overall testing of the hypothesis can be concluded that in the functional food products, a more effective used is a negative message framing. Consumers feel less risk perception in functional food advertisements with a negative message framing. Source credibility is more effectively used in functional food products is high source credibility. Consumers feel less risk perception in functional food advertisementsdelivered by endorser with high source credibility.Keywords: functional food, message framing, source credibility, consumer risk perception